The Relationship Study Between Teachers' Perceptions Toward Organizational Culture and Their Job Satisfaction at a Polytechnic in Henan, China - Xiaoqing, Wang; Ye, Yan (Scholar: Human Sciences, 2021)
The aim of this study was to analyze the relationship between teachers’ perceptions towards organizational culture and their job satisfaction at the Polytechnic in Henan, China. The participants were 60 full-time teachers from Economics and Management department during academic year 2019 at a Polytechnic in Henan, China. In this study, two major research instruments were used to identify respective research objectives. The researcher adopted the survey including two parts: the part of organizational culture based on Saravanan (2013) and the part of job satisfaction based on Herzberg's (1959) Two-Factor Theory. The collected data was analyzed by Descriptive Statistics, Frequency and Percentage, Mean and Standard Deviation, and Pearson Product Moment Correlation Coefficient. The study results indicated that the level of teachers’ perceptions of organizational culture was High, and their Job Satisfaction was High. Consequently, it was determined that the relationship between the two variables was found to be Significant, it was interpreted that the relationship between the two was positive due to the correlation (r) value of .702. This study provided some information for the school leaders to understand teachers’ job satisfaction toward organizational culture in the school. It was recommended that teachers should evaluate whether their teaching behaviors are optimized, pay attention to the quality of teaching work, improve their professional ability to achieve career path.